Model Panca Krama /COACHEE Model (Commitment, Analysis, Choice, Execution, Evaluation): Alternatif Strategi Pengembangan Kompetensi Aparatur Sipil Negara di Indonesia - Sobandi, Baban; Nugraha, Hari; Dawud, Joni (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2025)
This study aims to formulate and validate an alternative model of Civil Servant (ASN) competency development strategy in Indonesia. This is because competency development is an obligation for every ASN. However, there are still many agencies that have not facilitated it properly, because they have not conducted an analysis of competency development needs and there are no Job Competency Standards. As a result, competency development is partial and not in line with organizational needs. The research was conducted using a mixed method. It begins with a literature review to construct the model, followed by validation and reformulation through triangulation. Validation sites include Pusjar SK TASNAS-LAN, BPSDM of West Java Province, and BKD of Garut Regency, with data collected from Agency Leaders, Division Heads/Coordinators, and Employees. The findings confirm the COACHEE Model as a relevant alternative strategy for ASN competency development. This model emphasizes the importance of commitment; needs analysis based on Activity Competency Standards (SKA); selection of forms and pathways aligned with levels and gap components; implementation integrated with IKU; and an evaluation system tied to IKU and SKP. Recommendations include embedding competency development commitments in planning documents, adopting SKA as an alternative in AKPK, selecting forms and pathways based on levels and gaps, accelerating the Corporate University (Corpu) system for integration with IKU, and establishing an evaluation system that measures IKU and SKP achievement